What's in a name? From minimum wages to living wages in Europe. (August 2019) - Schulten, Thorsten; Müller, Torsten
The development of a European minimum wage policy is back on the political agenda. While in the past the debate about a European minimum wage policy was largely detached from developments at national level, more recently the debate has been based on various national-level initiatives to ensure a living wage that enables workers and their families to enjoy a decent standard of living. Based on an introduction to the living wage concept, this article analyses how recent living wage initiatives in several EU Member States and the development of a European minimum wage policy could mutually reinforce each other and eventually result in a European living wage policy. In view of the significant heterogeneity of minimum wage regimes and welfare state traditions across Europe, the article calls for a pragmatic approach that adopts a common European target of 60 per cent of the national median wage as the benchmark for an adequate minimum wage.